Chapter 6 'In the Hospital + Out of the Hospital' Nurses and Nursing in Margaret Harkness's Periodical Publications - Janssen, Flore (Taylor & Francis, 2023)
In 1884, an article entitled 'Hospital Nurses', describing the role and responsibilities of nursing staff in hospital wards, appeared in the Leisure Hour. The author, who signed herself simply 'M. E. H.', was Margaret Elise Harkness, who, a few years later, would publish a series of novels on the conditions of the urban working poor under the pseudonym 'John Law'. Harkness had been working as a professional writer, mainly for the periodical press, since 1881; prior to this she had spent several years training and working as a nurse and dispenser in various London hospitals. 'Hospital Nurses' describes nursing as a profession, stating: 'Let no one imagine that this is work which all women can do.' Nurses, Harkness explains, are marked out by their abilities, not their social class, as the work relies on cooperation and equal interaction between nurses of different class backgrounds. Although she gave up professional nursing, the voices of nurses and other medical practitioners are heard throughout Harkness's long writing career. Nurses appear as characters and commentators in her work; but she also continued to invoke her own medical knowledge for decades after she abandoned her training. For instance, she used periodicals as platforms to give medical advice on epidemics she witnessed in Australian mining communities around the turn of the twentieth century. This chapter traces the voices of nurses as female professionals through Harkness's contributions to periodicals from the 1880s to the beginning of the twentieth century.